The Use of water in 19th century landscape gardens as represented on cadastral maps - Gyurasza, Miklós; Sárospataki, Máté (4D Journal of Landscape Architecture and Garden Art, 2024)
The landscape gardens within the boundary of present-day Hungary can be clearly discerned in the cadastral maps of the Habsburg Empire. Although these maps record the state from a limited and narrow time period, they provide a very good overview of the gardens that existed in the second half of the 19th century. The importance of the use of water in landscape gardens is demonstrated by the fact that nearly 40% of the parks recordedon the maps at the time contained built or natural water features which were considered worthy of depiction. Our research has revealed the role of water in the landscape gardens of Hungary in a given period, the forms in which it appeared, its typical locations in the layout of the parks, and the distribution of landscape gardens with a water feature by county.